Study on synchronisation capability enhancement of optoelectronic oscillator using dynamic control bandpass filter. Issue 6 (1st December 2018) - Bishayee, Kousik; Mandal, Shantanu; Mukherjee, Arindum; Biswas, B. N.; Sarkar, Chandan K.
Abstract : This study introduces the concept of dynamic controlled bandpass filter (BPF) to achieve improved synchronisation capability of a single‐loop optoelectronic oscillator (OEO) under the effect of externally applied angle modulated signal. The governing equation for synchronisation ability of an OEO using dynamic control BPF has been derived. Theoretical study and comparison of locking capability enhancement using this dynamic BPF over a conventional static BPF are provided which is properly validated by simulation. Finally, the ability of frequency modulation to amplitude modulation conversion has been compared by measuring the total harmonic distortion values of the reconstructed signals.